Structural Dependence of Sulfated Polysaccharide for Diabetes Management: Fucoidan From Undaria pinnatifida Inhibiting α-Glucosidase More Strongly Than α-Amylase and Amyloglucosidase - Koh, H.S.A. (Frontiers Media S.A., 2021)
10.3389/fphar.2020.00831